Paradoxical arthritis occurring during anti-TNF in patients with inflammatory bowel disease: histological and immunological features of a complex synovitis. Issue 1 (9th April 2018) - Alivernini, Stefano; Pugliese, Daniela; Tolusso, Barbara; Bui, Laura; Petricca, Luca; Guidi, Luisa; Mirone, Luisa; Rapaccini, Gian Ludovico; Federico, Francesco; Ferraccioli, Gianfranco; Armuzzi, Alessandro; Gremese, Elisa
Abstract : Objective: Paradoxical arthritis under tumour necrosis factor inhibitor (TNF-i) for inflammatory bowel disease (IBD) has been described. This study aims to evaluate the histological features of paired synovial tissue (ST) and colonic mucosa (CM) tissue in patients with IBD developing paradoxical arthritis under TNF-i. Methods: Patients with IBD without history of coexisting joint involvement who developed arthritis under TNF-i were enrolled. Each patient underwent ST biopsy and ileocolonoscopy with CM biopsies. ST and CM paired samples were stained through immunohistochemistry (IHC) for CD68, CD21, CD20, CD3 and CD117. Clinical and immunological parameters (anticitrullinated peptides antibodies (ACPA)-immunoglobulin (Ig)M/IgA rheumatoid factor (RF)) were collected. Psoriatic arthritis (PsA) and ACPA/IgM-RF/IgA-RF negative rheumatoid arthritis (RA) were enrolled as comparison. Results: 10 patients with IBD (age 46.0±9.7 years, 13.2±9.9 years of disease duration, 2.5±1.6 years of TNF-i exposure, six with Crohn's disease and four with ulcerative colitis, respectively) were studied. At ST level, IHC revealed that patients with IBD with paradoxical arthritis showed more similar histological findings in terms of synovial CD68 +, CD21 +, CD20 +, CD3 + and CD117 + cells compared with PsA than ACPA/IgM-RF/IgA-RF negative RA. Analysing the CM specimens, patients with IBD showed the presence of CD68 +, CD3 +, CD117 + and CD20 + cells in 100%, 70%, 60% and 50% of cases, respectively, despite endoscopic remission. Finally, addition of conventional disease-modifying antirheumatic drugs and switch to ustekinumab were more effective than swapping into different TNF-i in patients with IBD with paradoxical arthritis. Conclusion: Patients with IBD may develop histologically proven synovitis during TNF-i, comparable to PsA. The inhibition of inflammatory pathways alternative to TNF (IL12/1L23) may be an effective therapeutic option for severe paradoxical articular manifestations.